O dever de diligência como instrumento de efetivação da proteção do meio ambiente: análise da proposta de regulamentação no direito europeu - Vieira, Stephanie Cristina de Sousa (2023)
Holding companies accountable for causing damage to the environment is a global challenge. Considering this reality and the worsening of climate change, the European Commission adopted a proposal for a directive on corporate sustainability due diligence, in order that all Member States regulate and implement the instrument in accordance with the guidelines set out in the regional standard. This will allow the evaluation and permanent monitoring of the risks of the activities of companies, including transnational ones, with the aim of protecting human rights, preventing environmental damage and promoting access to justice. From this, however, this question arises: What are the limitations of the European due diligence with regard to the effective protection of the environment? In this sense, the general objective of this research is to understand the obstacles to be faced and the perspectives of the aforementioned instrument with regard to the effective environmental protection in the EU, taking into account its proposed regulation at the regional level. To this end, in the three chapters of this work, specific objectives are explored, respecting the following order: i) to analyze the evolution of the concept of the due diligence, highlighting its direction towards a sustainable perspective; ii) to explain the spread of the instrument in the EU and the rationale for the need for its regional regulation; and iii) Understand the challenges that the due diligence, when legally established, may face, based on the proposal for a directive adopted by the European Commission. The methodology presents a qualitative nature with the application of inductive and deductive reasoning, through the bibliographic review, as well as through document analysis of international norms and regional instruments on the subject. As a result, it is understood that the regulation of the due diligence in the EU may contribute to regional and also global progress in terms of the environment, human rights and good governance, but, on the other hand, it may encounter limitations in its effectiveness, due to the approval of a less ambitious legal text and, therefore, inadequate to face the problems, especially the climate ones; the complexity of companies' value chains and the difficulties regarding the control and inspection of compliance with standardized provisions. It is concluded that this is an important instrument in view of the current circumstances, although there is a need for joint action with other mechanisms and improvement of its provisions, so that the protection of the environment is, in fact, effective.